The Relationship Between Pregnant Women's Nutritional Status and Newborn Weight - Siti Uswatun Hasanah; Widia Shofa Ilmiah (KHD Production, 2026)
Maternal nutritional status during pregnancy plays a crucial role in fetal growth and is a key determinant of newborn birth weight. Inadequate maternal nutrition increases the risk of low birth weight (LBW), which is strongly associated with increased neonatal morbidity and mortality. This study aimed to examine the relationship between maternal nutritional status during pregnancy and newborn birth weight. A facility-based analytical study with a case–control design was conducted at a Community Health Center. A total of 36 mother–newborn pairs were recruited using a 1:1 case–control ratio. Maternal nutritional status was assessed using anthropometric indicators recorded during pregnancy, and newborn birth weight was measured within 1 hour of delivery. Data were analyzed using the chi-square test with α = 0.05. The analysis revealed a statistically significant association between maternal nutritional status and newborn birth weight (p = 0.003). Mothers with adequate nutritional status were more likely to deliver infants with normal birth weight than those with poor nutritional status. Conversely, low birth weight was more frequently observed among infants born to mothers with inadequate nutritional status during pregnancy. Maternal nutritional status during pregnancy is significantly associated with newborn birth weight in this primary health care setting. Strengthening early nutritional screening and interventions for pregnant women is essential to reduce the risk of low birth weight and improve neonatal health outcomes.